Evaluation and Standardization of Herbal Extract of Carum Copticum - Pal, Sunil Kumar; Tandan, Manisha; Jain, Nishi Prakash (Journal of Biomedical and Pharmaceutical Research, 2024)
Plants are important and supplementary sources of drugs and Dietary. It can provide biologically active molecules which are used for treatments of different types of disease. The history of the medicinal plants is so important which explain the continuity and importance of medicated plants from generation to generation where and how it was discovered and who observed the medicinal importance in different era because the plants provide biologically active and important molecules that can be used for treatment of different disease. The present study was designed for the evaluation of herbal extracts for effective selection of plant material, standardization and extraction. Keywords: Extracts, Standardization, Extraction.